2003
DOI: 10.1108/00330330310484378
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and use of electronic information services: trends in UK higher education from the JUSTEIS project

Abstract: Urquhart, C., Lonsdale, R.,Thomas, R., Spink, S., Yeoman, A., Armstrong, C. & Fenton, R. (2003). Uptake and use of electronic information services: trends in UK higher education from the JUSTEIS project. Program, 37(3), 167-180. Sponsorship: JISCThe aim of the JUSTEIS project over the first three cycles (1999-2002) was to examine the uptake and use of electronic information services in higher education in the UK, so that planning of JISC services could be informed by trends in usage and evidence of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 13 publications
3
45
0
Order By: Relevance
“…(P4Y1T1) Thus we can see that she is using a variety of different techniques to finding information. Her reliance on other people for advice confirms Urquhart et al (2003)'s finding that students rely on the opinion of peers when searching for information. Indeed, we found that throughout the study students regularly reported using particular strategies or resources because they knew their peers were doing so.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…(P4Y1T1) Thus we can see that she is using a variety of different techniques to finding information. Her reliance on other people for advice confirms Urquhart et al (2003)'s finding that students rely on the opinion of peers when searching for information. Indeed, we found that throughout the study students regularly reported using particular strategies or resources because they knew their peers were doing so.…”
Section: Resultssupporting
confidence: 70%
“…Although numerous other studies of information seeking have used undergraduate students as their participants, including , Whitmire (2002), Fescemyer (2000, Kim (2003), Wilson et al (2002aWilson et al ( , 2002b, , Cothey (2002), Cole et al (2005), Urquhart et al (2003Urquhart et al ( , 2005, and Urquhart , they have tended to concentrate on how specific search tasks are carried out rather than tracking change over time. Although Whitmire (2002) studied the way that information seeking is related to the development 5 of epistemology in undergraduates, she focused on the results of the process, rather than its early development, and thus took final year undergraduates as her sample.…”
Section: Studying the Development Of Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…Student reactions to what they find are classically considered under the relevance of information retrieval research, although relevance is a multi-dimensional construct (Schamber et al, 1990) and -for students, at least, gets mixed up with convenience of access to full text (Connaway et al, 2011, Urquhart et al, 2003b). Steinerová's (2008) conclusion that relevance is linked to 'value', 'utility', and 'importance' may be diluted by the convenience of availability, and pertinence a more accurate description than relevance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This range of sources was used to try and obtain the right information for a particular task as found elsewhere (Urquhart et al, 2004, Urquhart et al, 2003b. All students in this research used physical sources (reference/reading lists, books, journals) and subscribed resources (databases), with books and journals the primary targets.…”
Section: Qualitativementioning
confidence: 99%